Evaluation of The Impact of Photovoltaic Laboratories Development on Higher Education and Industry - SIREGAR, MARSUL; PARDOSI, CRISTONI HASIHOLAN; BACHRI, KAREL OCTAVIANUS; NUR, TAJUDDIN; PANDJAITAN, LANNY W. (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2024)
ABSTRAK Transisi energi dari energi konvensional ke energi terbarukan semakin meningkat, sejalan dengan kesadaran akan keberlanjutan penggunaan energi terbarukan secara global. Laboratorium Fotovoltaik Universitas Katolik Indonesia Atma Jaya berkapasitas 5,2 kWp dikembangkan untuk mendukung pendidikan dan pelatihan industri. Tulisan ini menjelaskan dampak positif Laboratorium terhadap sudut pandang mahasiswa dan industri, yaitu tentang kinerja panel surya, evaluasi sistem on-grid dan off-grid, serta pemeliharaan system. Berdasarkan kepuasan mahasiswa disimpulkan sangat puas dan puas berkisar 93,17%, dengan rincian sangat puas 50,14%, dan puas 43,03%. Sedangkan Industri menunjukkan sangat puas dan puas sebesar 93,96%, dengan rincian sangat puas 44,99%, dan puas 48,97%. Kata kunci: Fotovoltaik, Energi Surya, Pendidikan Tinggi, Studi Eksploratori.  ABSTRACT The energy transition from conventional energy to renewable energy is increasing, in line with the awareness of the sustainability of renewable energy use globally. The Atma Jaya Catholic University Photovoltaic Laboratory with a capacity of 5.2 kWp was developed to support industrial education and training. This paper describes the positive impact of the Laboratory from the perspective of students and industry, namely on the performance of solar panels, evaluation of on-grid and off-grid systems, and system maintenance. Based on student satisfaction, it is concluded that very satisfied and satisfied are around 93.17%, with details of very satisfied 50.14%, and satisfied 43.03%. While the industry shows very satisfied and satisfied of 93.96%, with details of very satisfied 44.99%, and satisfied 48.97%. Keywords: Photovoltaic, Solar Energy, Higher Education, Exploratory Study.